Extensive disease among potential candidates for hemi‐ablative focal therapy for prostate cancer. (13th December 2019) - Takeda, Toshikazu; Tin, Amy L; Corradi, Renato B; Alvim, Ricardo; Hashimoto, Takeshi; Ito, Yujiro; Nguyen, Daniel P; Mamoor, Maha; Robertson, Nicola L; Vargas, Hebert A; Benfante, Nicole E; Sjoberg, Daniel D; et al.
Abstract : Objective: To examine a set of proposed eligibility factors for hemi‐ablative focal therapy in prostate cancer and to determine the likelihood of residual extensive disease. Methods: We retrospectively analyzed data from 98 patients with unilateral prostate cancer on biopsy with detailed tumor maps from whole‐mount slides and preoperative magnetic resonance imaging data. These patients met the focal therapy consensus meeting inclusion criteria (prostate‐specific antigen <15 ng/mL, clinical stage T1c‐T2a and Gleason score 3 + 3 or 3 + 4 on needle biopsy), and underwent radical prostatectomy between 2000 and 2014. Extensive disease was defined as having Gleason pattern 4/5 in bilateral lobes, any extraprostatic extension, seminal vesicle invasion or lymph node invasion. Both lobes of the prostate were scored on magnetic resonance imaging. Preoperative characteristics including biopsy and magnetic resonance imaging data were used to predict extensive disease. Results: Among our cohort of 98 patients, 40% (95% CI 30–50%) had extensive disease. A total of 33% (95% CI 24–43%) had Gleason pattern 4/5 in both lobes with a median Gleason pattern 4/5 tumor volume in the biopsy negative lobe of 0.06 cm 3, 17 patients had pathological tumor stage ≥3 and one patient had lymph node invasion. Conclusions: An important number of patients meeting the focal therapy consensus meeting inclusion criteria can present extensive disease. Further studies using targeted biopsies might provide more accurate information about the selection of focal therapy candidates.